Low‐Ir IAB irons from Morasko and other locations in central Europe: One fall, possibly distinct from IAB‐MG. (14th December 2013) - Pilski, A. S.; Wasson, J. T.; Muszyński, A.; Kryza, R.; Karwowski, Ł.; Nowak, M.
Abstract Differences in texture and discovery location prompted us to analyze 16 irons from Morasko; one from Seeläsgen, known to have a similar composition; and a new mass found at Jankowo Dolne. These were analyzed in duplicate by instrumental neutron‐activation analysis (INAA). The results show that all 18 samples have very similar compositions, distinct from all other IAB irons except Burgavli; we conclude that they are all from a single shower. Eight of the samples were from regions with large amounts of cohenite (but were largely free of inclusions) and six were from samples with very little cohenite; we could find no resolvable difference in composition between these sets, a fact that suggests that the C contents of the metal phases were similar in the two areas. Although Morasko has been classified into the IAB main group (IAB‐MG), its Ir plots well outside the main group field on an Ir‐Au diagram. We considered the possibility that the low Ir reflected contamination by a melt from a IAB region that ponded and experienced fractional crystallization; however, because Morasko has Pt, W, and Ga values that are the same as the highest values in IAB‐MG, we rejected this model. We therefore conclude that Morasko formed from a different melt than the IAB‐MG irons; the Morasko melt was produced by impact heating, but one or more of the main Ir carriers did not melt, leaving much of the Ir in the unmelted residue. Copper is the only element that shows resolvable differences among Morasko samples. Most (13 of 18) samples have 149 ± 4 μg g−1 Cu, but three have 213 ± 10 μg g−1; we interpret this to mean that the low‐Cu samples have equilibrated with a Cu‐rich phase, whereas there was none of the latter phase within a few diffusion lengths of the samples with high Cu contents.